Financial Literacy and Loan Terms Affect Msme Formal Credit Access - Nugraeni Nugraeni; Ratri Paramitalaksmi; Zaenal Wafa; Kiki Saputri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The rapid increase in Micro, Small and Medium Enterprises (MSMEs) in Indonesia is able to encourage economic growth. The existence of government policies on financing Micro, Small and Medium Enterprises (MSMEs) motivates Micro, Small and Medium Enterprises (MSMEs) entrepreneurs to be able to create a good financing system so as to affect the ease of accessing credit.  Ease of access to formal credit is important because formal credit providers have more availability of funds than informal credit providers. Access to formal credit carried out on Micro, Small and Medium Enterprises (MSMEs) is also based on the banking behavior of Micro, Small and Medium Enterprises (MSMEs) entrepreneurs who are influenced by financial literacy.  Various efforts made by the Office of Cooperatives and MSMEs of Sleman Regency, Yogyakarta Special Region, Indonesia in improving financial literacy include providing financial training that is analyzed for effectiveness in research.  This study aims to determine the effect of financial literacy and credit requirements on access to formal credit by Micro, Small and Medium Enterprises (UMKM) in Sleman Regency, Yogyakarta Special Region, Indonesia. The method used in this study is a regression test.  The results of this study show that financial literacy and credit requirements can affect access to formal credit by Micro, Small and Medium Enterprises (MSMEs) in Sleman Regency, Yogyakarta Special Region.